Applying a Spectral Method to Solve Second Order Differential Equations With Constant Coefficients (2019)
Spectral methods have been successfully applied to numerical simulation in a variety of fields, such as heat transfer, fluid dynamics, quantum mechanics and so on. They are powerful tools for the numerical solutions of differential equations, ordinary and partial. This paper presents a spectral method based on polynomial interpolation nodes distributed according to Chebyshev grids, to solve a second order ordinary differential equation with constant coefficients. It demonstrates the accuracy of this method as compared to finite difference method and this advantage is theoretically explained